Driving Sustainable Change: Understanding How Management Talent Practices Mediates Knowledge Sharing And Employee Engagement For Green Innovation Behavior In SMEs - Arraniri, Iqbal; Dahl, Martin; Rois, Tatang; Prayudi, Deri; Komarudin, Munir Nur (Indonesian Journal of Strategic Management, 2025)
This study investigates the mediating role of management talent practices in the relationship between knowledge sharing, employee engagement, and green innovation behavior within small and medium-sized enterprises. Drawing upon the resource-based view, this research posits that effective MTP serves as a crucial organizational resource, fostering a work environment conducive to KS, EE, and ultimately, GIB. SMEs, often facing resource constraints, must strategically leverage talent management to promote sustainable practices. This study examines how employee engagement and knowledge sharing related to environmental sustainability. The research explores how these factors collectively contribute to green innovation behavior, encompassing the development and implementation of environmentally friendly products, processes, and practices. By analyzing the mediating effect of MTP, this study aims to provide valuable insights for SME managers and policymakers seeking to promote a more sustainable and innovative business ecosystem. The findings contribute to the growing body of literature on sustainable change through effective talent management strategies, offering practical recommendations for fostering green innovation within resource-constrained environments.